1979
DOI: 10.1128/aac.16.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Australian evaluation of Autobac I with suggested interpretive and technical modifications

Abstract: Autobac I, a recently introduced semiautomated method for rapid antibiotic susceptibility testing, has been evaluated by comparison with the calibrated dichotomous sensitivity disk diffusion technique, which is routinely used in many Australian hospitals. Only the most common clinical isolates, Staphylococcus aureus, Escherichia coli, Klebsiella sp., and Proteus mirabilis, were included in this evaluation, and an overall interpretive agreement of 93% was obtained. However, an unusually high rate of discrepancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
1

Year Published

1980
1980
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
9
1
Order By: Relevance
“…Thus, a "false" reading of susceptible could be obtained with the Autobac I system, depending on the ratio of susceptible strains to resistant strains selected for testing. An extended period of incubation of the Autobac I cuvette has been suggested as a remedy for the erroneous results obtained with S. aureus and the penicillins (3). Our results also indicate that a decrease in the LSI upon extended incubation of the cuvette could serve as a marker for detecting such a mixture.…”
supporting
confidence: 49%
See 3 more Smart Citations
“…Thus, a "false" reading of susceptible could be obtained with the Autobac I system, depending on the ratio of susceptible strains to resistant strains selected for testing. An extended period of incubation of the Autobac I cuvette has been suggested as a remedy for the erroneous results obtained with S. aureus and the penicillins (3). Our results also indicate that a decrease in the LSI upon extended incubation of the cuvette could serve as a marker for detecting such a mixture.…”
supporting
confidence: 49%
“…In an initial collaborative study, the performance of this system was shown to have a high overall level of agreement (91.5%) with the disk diffusion method (7). However, a number of discrepancies have been reported for several organism-antibiotic combinations (1,3,4,6,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, some organisms when tested with certain antimicrobial agents produced agreements of less than 90%, including Staphylococcus aureus tested with penicillin G (85.3%). Other workers noted similar disagreements with ampicillin and penicillin (4)(5)(6). Testing of the same strains on subsequlent days results in some strains demonstrating a susceptible result one day and a resistant result the next (9).…”
mentioning
confidence: 85%